Mechanization of Sugarcane Planting - Singh, A K; Singh, Sukhbir (Indian Farming, 2017)
Mechanization of sugarcane planting facilitates timely completion of different operations with reduced labour, human drudgery and cost of operation. Furrow method of planting in deep furrows has been found superior in comparison to flat method of planting in terms of increased yield, reduced lodging and better ratooning due to deep rooting of crop. This method also facilitates furrow irrigation which increases irrigation water use efficiency (IWUE) and saves irrigation water.